Semiotic resources of gustatory modality in healthy beverage advertising (based on English) - Rybalchenko, Andrii (Current issues of Ukrainian linguistics: theory and practice, 2025)
This article analyzes semiotic resources used to describe gustatory qualities of juice, sparkling water, functional beverages, tea, coffee, and plant-based milk on the websites of 25 beverage manufacturers. Lexical units are analyzed in terms of their meaning, frequency, combinability, emotional valence, degree of intensity, and multisensoriality while semiotic elements are examined in terms of meaning potentials and alignment with the verbal part of the advertising messages. Traditionally, the sense of taste received less attention from scholars than other senses, however, this has started to change in recent years. In particular, the language of taste and flavor is important for advertisers, as it helps to increase the sensory appeal of marketed products. This is not least because of the link between taste modality and emotional reactions, which influence consumer preferences and behaviors. For this reason, advertisers emphasize both gustatory characteristics and healthfulness of beverages even though healthy foods are traditionally perceived as not very enjoyable in taste. Taste and healthfulness are linked in product descriptions with the help of stylistic devices such as alliteration, assonance, parallelism, and personification. Rich taste is highlighted via hyperbole, metaphor, and evaluative adjectives that act as intensifiers. Healthfulness is emphasized via the link between taste and its natural source, verbalized with the help of nuanced terms and grammatical constructions. Adjectives of the interoceptive modality are used to establish a connection between taste and well-being. Scalar language is used to convey the subtleness of taste, which aligns with a health-conscious mindset. Furthermore, the findings demonstrate that visual elements such as color and imagery complement gustatory descriptions, reinforcing brand messages of health and transparency. The findings contribute to sensory linguistics and marketing by revealing strategies and means used to convey taste perception in a way that aligns with modern consumer values of health and naturalness. This interdisciplinary study bridges linguistics, marketing, and semiotics, and may be of interest to researchers and industry professionals.